IELTS graduation : (Macmillan publisher limited, 2007)
IELTS Graduation is a motivating and comprehensive course for the students preparing to take the International English language Testing System examination. Aimed at those in the IELTD band of 5.5 and above, this topic-based book will train students in the skills required to increase their IELTS score.